2020
DOI: 10.1038/s41598-020-67367-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution, morphological, optical and electrical properties of femtosecond pulsed laser deposited TiO2 thin films

Abstract: In this paper, we report anatase and rutile titanium oxide (TiO2) nanoparticulate thin films fabricated on silica and Indium Tin Oxide (ITO) substrates using femtosecond pulsed laser deposition (fs-PLD). Depositions were carried-out at substrate temperatures of 25 °C, 400 °C and 600 °C from anatase and rutile phase target materials. Effect of substrate temperature on the surface morphology, microstructural, optical, and electrical properties of these films were systematically investigated by using various rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…The vibrational bands of anatase TiO 2 material has centered at 137, 207, 414, 519 and 644.8 cm −1 , respectively, corresponding to the Raman active modes of Eg, Bg, B1g, A1g, and Eg as showed in inserted Fig. 5 [26,27]. It can be concluded that strong anatase peak at 137 cm −1 .…”
Section: Resultsmentioning
confidence: 86%
“…The vibrational bands of anatase TiO 2 material has centered at 137, 207, 414, 519 and 644.8 cm −1 , respectively, corresponding to the Raman active modes of Eg, Bg, B1g, A1g, and Eg as showed in inserted Fig. 5 [26,27]. It can be concluded that strong anatase peak at 137 cm −1 .…”
Section: Resultsmentioning
confidence: 86%
“…Various coating methods have been investigated in the literature, for the deposition of Ti and Ti:X (X = heteroatom other than Ti) thin films onto ITO and FTO. Among them, satisfied adhesion of the Ti or Ti:X layer to the substrate has been reported using physical deposition techniques including radio-frequency (RF), pulsed direct current (DC) sputtering, and pulsed laser deposition (PLD) by adjusting the substrate’s temperature in the range of 400–500 °C [ 27 , 28 , 29 ].…”
Section: Description Of Deposition Techniques Of Tco-ti: Metal Thin F...mentioning
confidence: 99%
“…Pulsed laser deposition is a technique that has been also widely utilized for preparing Ti:X layers onto indium tin oxide [ 29 , 36 ]. The morphological features and the electrical properties of Ti:X film deposited onto the TCO can be controlled by varying substrate temperature.…”
Section: Description Of Deposition Techniques Of Tco-ti: Metal Thin F...mentioning
confidence: 99%
See 2 more Smart Citations